Characterization of flavor compounds and core functional microorganisms during pile fermentation of Liupao tea - Yanjun Chen; Yuelan Pang; Yueming Liang; Zhusheng Liu; Zhonghua Liu; Qiming Hu; Fujing Pan (Food Chemistry, 2026)

Efficient identification of allergenic epitopes and analysis of the peptide recognition mechanism in tropomyosin of prawn (penaeus chinensis) through quantum chemistry computational framework - Xiangfei Hu; Qiannan Jiang; Hui Wang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2026)

High magnetic field-driven assembly of collagen peptide-cerium chelates from fish skin: Microstructure, colloidal stability and absorption behavior - Peihan Wu; Hui Wang; Yueming Hu; Pingwei Wen; Liang Zhang; Peng Zhang; Xiaomei Sha; Zongcai Tu (Food Hydrocolloids, 2026)

Mechanistic insights into pulsed electric field-induced oxidative degradation of arginine and glutamic acid: Combined experimental characterization and DFT computation - Xiangfei Hu; Qiannan Jiang; Zongcai Tu; Yueming Hu; Hui Wang (Food Research International, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

In-situ constructed Ag/CNT hierarchical networks in TPU nanofibers for dual-mode triboelectric sensing - Shiqiang Ouyang; Feijie Wang; Yichi Liu; Suyang Wang; Yaoli Wang; Yuefan Liu; Zhixuan Mei; Kaixin Liao; Shenzhuo Zhang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Exploring relaxation features for rapid identification of olive oil adulteration via low-field nuclear magnetic resonance integrated with chemometrics - Yulong Chen; Xuewen Qin; Shan Zeng; Bing Li; Yueming Tao; Huanjun Hu (Food Research International, 2026)

Arbuscular mycorrhizal symbiosis enhances microbial contribution to mineral-associated organic carbon persistence in soil: Insights from soil microbial community and microbial necromass carbon - Yin LIU; Jin QIAN; Yueming ZHU; Jing HU; Bianhe LU; Yuxuan HE; Junwei SHEN (Pedosphere, 2026)

Engineering design paradigms for high-performance rotating triboelectric nanogenerators: From structural optimization to system synergy - Yan Ma; Feijie Wang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Corrigendum to “Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation” [Food Res. Int. 213 (2025) 116593] - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2026)

High magnetic field-assisted preparation of food-derived collagen peptide-cerium (III) chelate: reducing oxidative stress and helping restore osteoblast function - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu (Food Bioscience, 2025)

Molecular mechanisms of superheated steam-induced modifications enhancing ovalbumin functional properties: Insights from site identification and peptidomic analysis - Haiqi Chen; Zuohua Xie; Feifei Wang; Zongcai Tu; Pingwei Wen; Siqiong Zhang; Hui Wang; Yueming Hu (Food Chemistry, 2025)

Modulating immune reactivity of grass carp parvalbumin via pulsed electric field-induced variation of structural properties - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Investigation of the mechanism of H2O2 combined pulsed electric field treatment reducing the antigenicity of parvalbumin and tropomyosin by high-resolution mass spectrometry, molecular dynamics and DFT computation - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Jie Cheng; Haibin Liu; Yueming Hu; Zongcai Tu (Innovative Food Science & Emerging Technologies, 2025)

Chelation of cerium (III) with fish skin collagen peptides: Improving the in vitro stability and bioavailability of inorganic cerium - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu; Jie Cheng; Hai-bin Liu; Pingwei Wen (Food Research International, 2025)

A novel mutation type S420I in Myosin-5 confers resistance to Phenamacril in Fusarium fujikuroi - Yueming Jin; Zelong Peng; Zhili Yuan; Furong Chen; Feng Hu; Hongzhou Chen; Yiping Hou (Pesticide Biochemistry and Physiology, 2025)

Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2025)

Passive Synthetic Aperture for Direction-of-Arrival Estimation Using an Underwater Glider with a Single Hydrophone - Yueming Ma; Jie Sun; Shuo Li; Tianze Hu; Shilong Li; Yuexing Zhang (Journal of Marine Science and Engineering, 2025)
This paper addresses the aperture limitation problem faced by array-equipped underwater gliders (UGs) in direction-of-arrival (DOA) estimation. A passive synthetic aperture (PSA) method for DOA estimation using a single hydrophone mounted on a UG is proposed. This method uses the motion of the UG to synthesize a linear array whose elements are positioned to acquire the target signal, thereby increasing the array aperture. The dead-reckoning method is used to determine the underwater trajectory of the UG, and the UG’s trajectory was corrected by the UG motion parameters, from which the array shape was adjusted accordingly and the position of the array elements was corrected. Additionally, array distortion caused by movement offsets due to ocean currents underwent linearization, reducing computational complexity. To validate the proposed method, a sea trial was conducted in the South China Sea using the Haiyi 1000 UG equipped with a hydrophone, and its effectiveness was demonstrated through the processing of the collected data. The performance of DOA estimation prior to and following UG trajectory correction was compared to evaluate the impact of ocean currents on target DOA estimation accuracy.

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Calcium hypochlorite coupled with ultrasound pretreatment enhances methane production from sludge anaerobic digestion - Jiawei Hu; Shaogang Hu; Yueming Han (Journal of Environmental Chemical Engineering, 2025)

MAPK signaling mediated intestinal inflammation induced by endoplasmic reticulum stress and NOD2 - Siyuan Peng; Yan Zhao; Wang Jiang; Yan Long; Tian Hu; Mengling Li; Jinyue Hu; Yueming Shen (Molecular and Cellular Biochemistry, 2025)

Construction of W/O/W microcapsules based on the combination of polyglycerol polyricinoleate/protein for the co-encapsulation of crocin and quercetin: Physical properties, stability and in vitro digestion - Wei Fan; Yan Shi; Yueming Hu; Shu Wang; Jing Zhang; Wei Liu (Food Chemistry, 2025)

What drives embodied carbon policy? A global perspective on adoption - Ming Hu; Yueming Qiu; Ali Nouri (Environment, Development and Sustainability, 2025)
Embodied carbon refers to the greenhouse gas emission associated with the lifecycle of buildings. Embodied carbon policies are critical for addressing the environmental impact of construction materials and advancing climate goals. Despite their importance, the adoption of embodied carbon policies has been limited globally, influenced by economic, environmental, institutional, and trade factors. This study employs structural equation modeling to analyze 37 countries, testing ten hypotheses across four categorical factors. The base model reveals the significant influence of environmental vulnerability and institutional frameworks on policy adoption, while robustness models confirm the critical role of trade dependencies and economic competitiveness in shaping national embodied carbon strategies. Findings underscore that countries with high climate vulnerability and strong institutional support are more likely to adopt embodied carbon policies. Conversely, trade-reliant nations face challenges balancing competitiveness and sustainability. Policy implications suggest the need for international collaboration to align trade policies with carbon reduction goals, targeted support for vulnerable nations, and the integration of embodied carbon considerations into existing climate frameworks. These results offer a roadmap for policymakers to design more effective and equitable embodied carbon policies, fostering global progress toward sustainable construction and decarbonization.

Mechanism studies of gliadin-glucose glycation reaction and products formation by heat treatment with different conduction modes - Qiannan Jiang; Xiangfei Hu; Zongcai Tu; Pingwei Wen; Yueming Hu; Siqiong Zhang; Hui Wang; Zuohua Xie (Food Chemistry, 2025)

Identification of novel natural anti-browning agents based on phenotypic and metabolites differences in potato cultivars - Yueming Tang; Yiwen Yang; Fangyao Luo; Jinghong Luo; Jianjun Hu; Haoqiang Yu; Wanchen Li; Jia Gao; Fengling Fu (Food Chemistry, 2025)

Modulating allergenicity of prawn tropomyosin (penaeus chinensis) via pulsed electric field-induced conformational changes - Xiangfei Hu; Hui Wang; Yueming Hu; Pingwei Wen; Xiongchen Wu; Zongcai Tu (Food Chemistry, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Review the antioxidant and angiotensin converting enzyme inhibitory peptides derived from fish: Preparation, structure-relationship, bioavailability and ameliorating strategies - Shu Wang; Lu Zhang; Hui Wang; Bizhen Zhong; Yueming Hu; Hongmei Yin; Zongcai Tu (Food Bioscience, 2024)

Magnetic field: A non-thermal technology in food processing - Shu Wang; Lu Zhang; Hui Wang; Wei Fan; Yueming Hu; Zongcai Tu (Food Control, 2024)

Sustainable utilization of cultivated land resources based on "element coupling-function synergy" analytical framework: A case study of Guangdong, China - Hao Yang; Runyan Zou; Yueming Hu; Lu Wang; Yingkai Xie; Zhengxi Tan; Zhiqiang Zhu; A.-Xing Zhu; Jianzhou Gong; Xiaoyun Mao (Land Use Policy, 2024)

Lithology and elevated temperature impact phoD-harboring bacteria on soil available P enhancing in subtropical forests - Fujing Pan; Qian Yang; Yueming Liang; Xuan Yu; Peilei Hu; Wei Zhang; Yuelan Pang (Science of The Total Environment, 2024)

Insight into the effects of pulsed electric field on the structure, aggregation characteristics and functional properties of whey proteins - Xiangfei Hu; Hui Wang; Yueming Hu; Zongcai Tu (Food Hydrocolloids, 2024)

Insight into the aroma and taste enrichment pattern in Chinese traditional braised soup based on HS-SPME-GC-MS and HS-GC-IMS - Feifei Wang; Debin Guo; Pingwei Wen; Haiqi Chen; Yueming Hu; Jun Li; Zongcai Tu; Hui Wang (Food Bioscience, 2024)

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Efficient preparation of oyster hydrolysate with aroma and umami coexistence derived from ultrasonic pretreatment assisted enzymatic hydrolysis - Junwei Zhang; Zongcai Tu; Zizi Hu; Yueming Hu; Hui Wang (Food Chemistry, 2024)

Insight into the molecular mechanism underlying the enhancement of antioxidant activity in ovalbumin by high-energy electron beam irradiation - Haiqi Chen; Zhongyue Bian; Pingwei Wen; Hui Wang; Yueming Hu; Zongcai Tu; Guangxian Liu (Food Chemistry, 2024)

Discrimination and characterization of different ultrafine grinding times on the flavor characteristic of fish gelatin using E-nose, HS-SPME-GC-MS and HS-GC-IMS - Jinghong Xu; Zongcai Tu; Hui Wang; Yueming Hu; Pingwei Wen; Xiaoliang Huang; Shu Wang (Food Chemistry, 2024)

The decrease of Ara h 2 allergenicity by glycation is determined by reducing sugar chain length and isomers - Ping Yang; Xumei Wang; Hui Wang; Yueming Hu; Pingwei Wen; Zongcai Tu (Food Chemistry, 2024)

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Comparison of ovalbumin glycation induced by high-temperature steaming and high-temperature baking: A study combining conventional spectroscopy with high-resolution mass spectrometry - Yueming Hu; Haiqi Chen; Yifan Yang; Siqiong Zhang; Zuohua Xie; Jiaojiao Liu; Qiannan Jiang; Jun Liu; Pingwei Wen (Food Research International, 2023)

Source Apportionment of Soil Heavy Metal(Loid)s in Farmland Using Diverse Models: A Comparative Assessment in the Yellow River Delta - Wei Huang; Shuhuan Wang; Lu Wang; Yingqiang Song; Yue Zhu; Hao Yang; Yingkai Xie; Yueming Hu (Journal of Marine Science and Engineering, 2023)
The rapid development of industrialization and urbanization has posed serious challenges for coastal farmland ecosystems. Source apportionment of soil heavy metals is an effective way for the detection of non-point source pollution in farmland to help support the high-quality development of coastal agriculture. To this end, 113 surface soil samples were collected in the coastal delta of China, and the contents of As, Cd, Cr, Cu, Ni, Pb, and Zn were determined. A variety of models were integrated to apportion the source of soil heavy metals, including positive matrix factorization (PMF), geographical detector (GD), eXtreme gradient boosting (XGBoost), and structural equation modeling (SEM). The result of PMF models revealed that there was collinearity between various heavy metals, and the same heavy metal may have a mixed source. The XGBoost model analysis indicated that there were significant non-linear relationships between soil heavy metals and source factors. A synergy between air quality and human activity factors was the key source of heavy metal that entered the study area, based on the results of the GD. Furthermore, the input path effect of heavy metals in the soil of the study area was quantified by SEM. The balance of evidence from the above models showed that air quality (SO2 and NO2) and factories in the study area had the greatest impacts on Cd, Cr, and Zn. Natural sources were dominant for Pb, while As, Cu, and Ni were contributed by soil parent material and factories. The above results led to the conclusion that there was a cycle path in the study area that continuously promoted the migration and accumulation of heavy metals in farmland soil; that is, the heavy metals discharged during oil exploitation and smelting entered the atmosphere and then accumulated in the farmland soil through precipitation, atmospheric deposition, and other paths. In this study, it is shown that a variety of models can be used to more comprehensively assess the sources of soil heavy metals. This approach can provide effective support for the rapid prevention and decision-making management of soil heavy metal pollution in coastal areas.

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Flavor substances of low-valued red swamp crayfish (Procambarus clarkii) hydrolysates derived from double enzymatic systems - Chujun Li; Zongcai Tu; Wenyu Liu; Chunlin Wu; Yueming Hu; Hui Wang (Food Research International, 2023)

Nitric oxide is involved in melatonin-induced cold tolerance in postharvest litchi fruit - Jialiang Liu; Wanli Zhang; Meijiao Hu; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Guoxiang Jiang (Postharvest Biology and Technology, 2023)

Construction of a Diagnostic Model for Distinguishing Benign or Malignant Bone Cancer by Mining miRNA Expression Data - Yueming Zhang; Jianwei Hu; Tao Li; Shizhu Hao; Xiaotang Wu (Biochemical Genetics, 2023)

Integration of metabolomics and proteomics analysis to explore the mechanism of neurotoxicity induced by receipt of isoniazid and rifampicin in mice - Xiaoyu Qu; Jie Ma; Huan Gao; Yueming Zhang; Jinghui Zhai; Jiawei Gong; Yanqing Song; Tingting Hu (NeuroToxicology, 2023)

Co-60 gamma irradiation induced ovalbumin-glucose glycation and allergenicity reduction revealed by high-resolution mass spectrometry and ELISA assay - Guang-xian Liu; Zong-cai Tu; Hui Wang; Yueming Hu; Wen-hua Yang (Food Chemistry, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

The Impact of Multiple Pond Conditions on the Performance of Dike-Pond Extraction - Jinhao Zhou; Wu Zhou; Qiqi Zhou; Yuanhui Zhu; Fei Xie; Shen Liang; Yueming Hu (Fishes, 2022)
Dike-ponds in fisheries often present multiple pond conditions such as pure, suspended sediment, water bloom, semidry conditions, etc. However, the impact of these conditions on the performance of extracting dike-pond from remote sensing images has not been studied. To solve this problem, we explore the existence of such impacts by comparing the performance of four rule-based methods in two groups of test regions. The first group has few multiple pond conditions, while the second has more. The results show that various measure values deteriorate as the proportion of multiple pond conditions in the regions increases. All four methods performed worse in the second group than the first, where the overall accuracy decreased by 8.80%, misclassification error increased by 3.69%, omission error raised by 10.53%, and correct quantity rate dropped by 8.23%, respectively. The extraction method that ingested multiple pond conditions performed indistinguishably from the other methods in the first group. However, it outperformed the other methods in the second group, with a 4.22% improvement in overall accuracy, a 10.25% decrease in misclassification error, and a 19.03% increase in the correct quantity rate. These findings suggest that multiple pond conditions can negatively impact the extraction performance and should be considered in dike-pond applications that require a precise pond size, number, and shape.

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Study on calculation and validation of tropospheric ozone by ozone monitoring instrument – microwave limb sounder over China - Yueming Hu; Huanhuan Yan; Xingying Zhang; Yi Gao; Xiangdong Zheng; Xuyan Liu (International Journal of Remote Sensing, 2020)

Detection of short-term urban land use changes by combining SAR time series images and spectral angle mapping - Zhuokun Pan; Yueming Hu; Guangxing Wang (Frontiers of Earth Science, 2019)

A comparison of building energy codes and policies in the USA, Germany, and China: progress toward the net-zero building goal in three countries - Ming Hu; Yueming Qiu (Clean Technologies and Environmental Policy, 2019)

Estimation of net primary productivity of forests by modified CASA models and remotely sensed data - Zhenhua Liu; Manqin Hu; Yueming Hu; Guangxing Wang (International Journal of Remote Sensing, 2018)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

Molecular characterization and evolutionary origins of farinin genes in Brachypodium distachyon L. - Saminathan Subburaj; Nana Luo; Xiaobing Lu; Xiaohui Li; Hui Cao; Yingkao Hu; Jiarui Li; Yueming Yan (Journal of Applied Genetics, 2016)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)

Spatial variability of soil arsenic and its association with soil nitrogen in intensive farming systems - Yueming Hu; Zhenglei Jia; Jiachang Cheng; Zhizhong Zhao; Feixiang Chen (Journal of Soils and Sediments, 2016)

Diagnosing Climate Change and Hydrological Responses in the Past Decades for a Minimally-disturbed Headwater Basin in South China - Yiping Wu; Dongsheng Cheng; Wende Yan; Shuguang Liu; Wenhua Xiang; Ji Chen; Yueming Hu; Qian Wu (Water Resources Management, 2014)

Research on the relationship between the fractional coverage of the submerged plant Vallisneria spiralis and observed spectral parameters - Qian Cheng; Kunqi Wu; Yan Bai; Yueming Hu (Environmental Monitoring and Assessment, 2013)

Integrating fuzzy logic with piecewise linear regression for detecting vegetation greenness change in the Yukon River Basin, Alaska - Yueju Xue; Shuguang Liu; Li Zhang; Yueming Hu (International Journal of Remote Sensing, 2013)

Characterization of seed hordeins and varietal identification in three barley species by high-performance capillary electrophoresis - Yueming Yan; Yi Jiang; Jianzhong Yu; Minhua Cai; Yingkao Hu; Dragan Perovic (Cereal Research Communications, 2003)